The Application And Marketing Strategies Of RFID Technology In Malaysia - Weng, Choy Wai (2002)
The problem under investigation will be to assess the factors affecting the market acceptance in relation to the implementation of the RFID. The purpose of this research is to provide Super Enterprise Sdn Bd with market opinion with regards to the acceptance of RFID implementation. procedure will include a review of related literature on findings of similar research , sample of public opinion through the design of survey format, analyze the survey results and finally conclude the finding of the research.